Collaborative Governance in Handling Neglected Children in Sukabumi City, 2022-2024 - Annisa Fauziah; M Rijal Amirulloh; Yana Fajar F.Y Basori (Prediksi : Jurnal Administrasi dan Kebijakan, 2026)
This study analyzes the collaborative governance process in handling neglected children in Sukabumi City from 2022 to 2024. The number of neglected children recorded during this period shows a concerning trend, with an average of only about 22% successfully handled. Using a descriptive qualitative method based on Ansell and Gash's (2007) collaborative governance model which consists of four dimensions: starting conditions, institutional design, facilitative leadership, and collaborative process data were collected through in-depth interviews with five key informant groups: the Department of Social Affairs (Dinas Sosial), Satpol PP (Civil Service Police Unit), DP2KBP3A, LKSA Ummi Kulsum, and IPSM (Community Social Workers Association). The findings indicate that the collaborative governance process has not functioned effectively. The four dimensions mutually reinforce weaknesses in a recurring cycle: unequal starting conditions, suboptimal facilitative leadership, inadequate institutional design, and a reactive collaborative process. The main constraints include the absence of an official decree establishing an interagency integrated team, the lack of a regular coordination forum, differing incentives among stakeholders, and a complaint-based service system. This study recommends the immediate issuance of an official decree establishing an interagency integrated team and the formation of a regular coordination forum to strengthen multi-stakeholder collaboration.